Autologous fat transfer to the subcutaneous tissue in the context of breast reconstructive procedures - Szychta, Pawel; Zadrozny, Marek; Rykala, Jan; Banasiak, Lukasz; Witmanowski, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Autologous fat transfer (AFT) is an appropriate technique for aesthetic rejuvenation of the face, aesthetic enhancement of hands, correction of the facial appearance in various disorders and constitutes a surgical alternative of treatment of numerous breast deformities ranging from distorting posttraumatic scars, post-eczema lesions, post-burn deformities to partial or total breast reconstruction. Our work is aimed to familiarize dermatologists with the technique of harvesting and implanting the aspirate of adipose cells in patients consulted for deformities of the breast. In addition, the review summarizes the most common applications of AFT in the breast reconstructive procedures. In summary, AFT is an oncologically safe, relatively complication-free, minimally invasive surgical technique, which can be used to correct a wide range of deformities, which are commonly seen by dermatologists, in the area of the face, trunk and extremities. The procedure can correct a wide range of breast deformities, from contour or single quadrant deformities up to the state after mastectomy.